Vivivary Tests on Mangrove Plants Species Rhizophora apiculata and Avicennia alba Against the Level of Salt Salinity and Tide - Pandu Prabowo Warsodirejo; Tika Santika; RA Rina Dian Anggraini; Widya Sari (Bioscience, 2021)
Indonesia's coastal areas have a large area and potential for mangrove ecosystems. Of the approximately 15,900 million ha of mangrove forests in the world. 27% or 4,293 million ha are in Indonesia. The Sicanang Medan Belawan mangrove forest, North Sumatra Province, is a wetland area which mostly consists of mangrove forests. In the mangrove forest, there are Rhizophora apiculata and Avicennia alba species. Mangroves have unique morphological characters as a form of adaptation to the environment, one of which is the salinity of sea water which is the level of salinity or salt content in seawater. In the mangrove forest of Sicanang Medan Belawan, there are Rhizophora apiculata and Avicennia alba species which have the characteristics of vivivar culture development. From the results of test 1 on the species Rhizopora apiculata, it was found that the highest salinity level at the muddy and sandy station was 30 ppm, and the highest pH was at 7.79, and at a temperature of 29 C. While for Avicennia alba the highest salinity value was obtained at 30.6 ppm, the highest pH was at 7.82. , and temperature at 29.5 C. Based on the results that different zoning could affect yield, the vivivary shape of mangroves also had an effect on yield. salinity affects mangroves to develop, the higher the salinity, the more difficult it is for the seeds to develop